Spontaneous electrochemical treatment for sulfur recovery by a sulfide oxidation/vanadium(V) reduction galvanic cell - Kijjanapanich,P. (Academic Press Inc., 2015)
© 2014 Elsevier Ltd.All rights reserved. Sulfide is the product of the biological sulfate reduction process which gives toxicity and odor problems. Wastewaters or bioreactor effluents containing sulfide can cause severe environmental impacts. Electrochemical treatment can be an alternative approach for sulfide removal and sulfur recovery from such sulfide rich solutions. This study aims to develop a spontaneous electrochemical sulfide oxidation/vanadium(V) reduction cell with a graphite electrode system to recover sulfide as elemental sulfur. The effects of the internal and external resistance on the sulfide removal efficiency and electrical current produced were investigated at different pH. A high surface area of the graphite electrode is required in order to have as less internal resistance as possible. In this study, graphite powder was added (contact area >633cm2) in order to reduce the internal resistance. A sulfide removal efficiency up to 91% and electrical charge of more than 400C were achieved when using five graphite rods supplemented with graphite powder as the electrode at an external resistance of 30Ω and a sulfide concentration of 250mgL-1.